Design and fabricate adjustable lab chair with back rest - Muhammad Zulfadhli, Roslane (2010)
Durable, functional and adaptable seating is essential for specialized workplaces. Muscle and spine disorders are two of the top ranking causes of inability to work. The long-term duration of these complaints means they cause about one third of all lost working days. A problem often caused by incorrect or neglected seating. Industrial and lab workplaces have different seating requirements to the office: moisture, chemicals, static, different table heights, different shifts, multiple users. Fitting the chair to the task, and the materials to the environment, creates the most productive and healthy solution. Industrial and lab seating typically needs to be adjustable for a wide range of body types, to take into account workers over multiple shifts who might share the same chair: a contrast to the office environment, where workers usually don't need to share task seating. Thus the ergonomic requirement for industrial seating is quite important.